Czy inwestorzy biorą pod uwagę społeczną odpowiedzialność biznesu? Świadectwa empiryczne z polskich spółek giełdowych - Kłysik-Uryszek, Agnieszka (Annales. Etyka w Życiu Gospodarczym, 2020)
The CSR (corporate social responsibility) concept has become an increasingly important part of corporations’ strategies and plans. However, it does not have to translate into investors’ decisions to buy their shares. The article investigates the relationships between companies implementing a CSR strategy, the rates of return on their stocks, and their investment risk. The paper aims to verify whether applying a CSR strategy affects stock market parameters (lower risk, higher investment profitability) and whether investors consider CSR companies less risky or more profitable and reliable than non-CSR firms. The following hypotheses have been formulated: (I) CSR companies are less risky (in terms of investment risk) than non-CRS ones; (II) CSR companies are characterized by higher rates of return than non-CSR ones.